Direct processing of alginate-immobilized microalgae into polyhydroxybutyrate using marine bacterium of Saccharophagus degradans. (May 2022) - Hu, Xinjuan; Meneses, Yulie E.; Stratton, Jayne; Huo, Shuhao
Graphical abstract: Highlights: Microalgae harvested from wastewater treatment was rich in carbohydrate and protein. S. degradans effectively degraded alginate-immobilized microalgae as carbon source. When pH was lower than 6 S. degradans growth was significantly inhibited. When glucose was available S. degradans degradation of alginate was repressed. PHB produced by S. degradans was degraded when available carbon source is limited. Abstract: Alginate immobilized microalgae (AIM) was found efficient in algal cells separation and pollutants removal, however, its processing required alginate removal. In present study, polysaccharide-degrading bacterium of Saccharophagus degradans was used to biodegrade alginate and microalgae in AIM and produce polyhydroxybutyrate (PHB). Results showed that AIM cultivated in wastewater contained 34.0% carbohydrate and 45.7% protein. S . degradans effectively degraded and utilized polysaccharide of AIM to maintain five-day continuous growth at 7.1–8.8 log CFU/mL. Compared with glucose, S . degradans metabolism of mixed polysaccharide in AIM maintained the medium pH at 7.1–7.8. Increasing the inoculum concentration did not enhance AIM utilization by S . degradans due to the carbon catabolite repression of glucose which likely inactivated hydrolysis enzymes. PHB production in S. degradans peaked at 64.9 mg/L after 72 h cultivation but was later degraded to provide energy. Conclusively, S. degradans was effective in direct processing of AIM while showing potential in PHB production.